Analysis of serum leptin levels as a biomarker in metabolic syndrome in type 2 diabetic patients in Okhla industrial area - Aggarwal, Juhi; Singh, Niharika; Kumar, Mayur (International Journal of Research in Medical Sciences, 2019)
Background: Metabolic syndrome is a progressive disorder which includes a wide array of disorders i.e. central obesity, hypertension, dyslipidemia, hyperglycemia, and insulin resistance. In patients with metabolic syndrome there is an increased risk of mortality due to coronary heart disease, stroke, vascular dysfunction etc. Obesity is one of the most crucial epidemics of modern times and hormone leptin plays an important role in regulation of body weight and energy balance. Methods: A total of 355 individuals were selected from the OPD, Department of general medicine at ESIC hospital, Okhla and it comprised of 196 males and 159 females suffering from type 2 diabetes mellitus with metabolic syndrome. The data was collected over a year i.e. June 2018 to July 2019. After baseline clinical and anthropometric evaluation, Fasting Blood Sugar (FBS), Post Prandial Blood Sugar (PPBS), lipid profile, Insulin (fasting), and leptin levels of the patients were analyzed. Results: Blood sugar fasting, blood sugar post prandial, lipid profile, leptin and insulin levels were increased significantly in female patients as compared to male patients with type 2 diabetic patients and metabolic syndrome. Conclusions: Based on the study results, it was found that leptin correlate significantly with metabolic syndrome and could be used as a biomarker for the early detection of the disease.